Development of Lift the Flap Book Learning Media on the Theme of Care About Living Things in Class IV SD - Nur Hanipah Tanjung; Beta Rapita Silalahi (PT Inovasi Pratama Internasional, 2023)
This study aims to develop learning media lift the flap book on the theme of caring for living things and to determine the feasibility of the media. This research is a type of development research (Research and Development) using the ADDIE development model. This research was carried out in three stages, namely 1) the analysis stage consisted of teacher analysis, student analysis; 2) the design stage, namely the design of the lift the flap book learning media using the Microsoft Word application and online applications that support it; 3) the development stage includes the validation stage. The subjects in this study were 2 media expert validators and 2 material expert validators. The instrument used to collect data is a questionnaire. The data analysis technique used in this research is descriptive qualitative and descriptive quantitative. Based on the feasibility of the media from the input of material experts, namely lecturers and teachers, media experts, namely lecturers. Reached 74%, material experts (teachers) reached 81%. If the proportion obtained reaches 60% to 80% then lift the flap book media is properly included. From the calculation above, it is obtained that the proportion is 74% and 81%, so the lift the flap book media is feasible. Media experts reach 90% and 85%. If the proportion obtained reaches 80% to 100% then the lift the flap book media is very feasible. From the calculation above, it is obtained that the proportion is 90% and 85%, so the lift the flap book is categorized as very good/very feasible. From the data validation results, the development of lift the flap book media on the theme of caring for living things developed by researchers was declared very feasible to be used as learning material in the learning process.